2022
DOI: 10.34127/jrlab.v11i3.647
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kemudahan Dan E-Wom Terhadap Keputusan Pembelian Layanan Streaming Netflix

Abstract: <p align="justify">Based on the reviews of potential customers, there are complaints in the form of difficulties in purchasing a Netflix subscription account. There are negative comments about the Netflix service through the Google Playstore service, indicating an electronic word of mouth problem. Customers who are willing to leave bad reviews and comments about Netflix, will create a bad perception of Netflix.This study aims to determine the Effect of Easy to use and E-WOM on Purchase Decisions on Netfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Several researchers have observed Sundanese traditional food from some regions. Durahmana et al (2022) described the naming of Sundanese foods in the Kuningan region. The result of the study showed that the naming of Sundanese foods in the Kuningan region has three lexical variations: phonological, morphological, and semantic.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have observed Sundanese traditional food from some regions. Durahmana et al (2022) described the naming of Sundanese foods in the Kuningan region. The result of the study showed that the naming of Sundanese foods in the Kuningan region has three lexical variations: phonological, morphological, and semantic.…”
Section: Introductionmentioning
confidence: 99%